Laporan Kasus : Pasien Anak 8 Tahun dengan Tonsilitis Kronik - Eka Putra, Muhammad Rafi; Imanto, Mukhlis (Medula, 2025)
Tonsillitis is one of the most common otorhinolaryngological (ENT) diseases in children, characterized by inflammation of the tonsils caused by recurrent or persistent infections. This condition has significant clinical implications as it may lead to respiratory disturbances, sleep disorders, and a decrease in overall quality of life if not managed comprehensively. Chronic tonsillitis is typically characterized by prolonged symptoms with recurrent episodes, often accompanied by tonsillar hypertrophy and obstructive manifestations. We report a case of an 8-year-old boy who presented with a sore throat that had persisted for three years prior to hospital admission, with worsening symptoms in the past month. The patient’s father reported a sensation of a lump in the throat, visibly enlarged tonsils, and frequent snoring during sleep. Physical examination revealed hyperemia of the soft palate, a midline uvula with edema and hyperemia, hyperemic pharyngeal mucosa, posterior arch that was difficult to assess, hyperemic tonsils with widened crypts and no detritus, and tonsil size graded T3–T2. Based on clinical history and physical findings, the diagnosis of chronic tonsillitis was established. Management of this condition requires a thorough evaluation of recurrence frequency, degree of airway obstruction, and its impact on systemic function to determine the appropriate therapeutic approach, either conservative or surgical, in order to prevent long-term complications.